"It's easier to take a pill than fix a problem:" qualitative analysis of barriers and facilitators to antimicrobial stewardship program implementation in carceral settings. - Tenner, Rebecca A; Grussing, Emily D; Manning, David.; Ngassa, Yvane.; den Berg, Jacob J; Vazquez, Gabriela Andujar.; Doron, Shira.; Campion, Maureen.; Wurcel, Alysse G (Tufts University. Tisch Library., 2024)
Keywords: Jails, Prisons, Antimicrobial resistance, Antimicrobial stewardship program, Qualitative research.; Springer Open.